Customizing Case-Based Learning (CBL) Sessions with Limited Resources and Analysis of their Perceived Effectiveness by the Conducting Facilitators - Sadia Ahsin , Hira Ashraf , Gul-e-Naghma, (Journal of Rawalpindi Medical College, 2020)
Introduction: Intense resource involvement invites educationists to think of innovative methods for the continuation of CBL sessions while remaining within the restricted budget. The current study was planned to develop CBL sessions for second-year MBBS class during the endocrine module utilizing minimal resources and to determine the effectiveness of customized CBL methods by qualitatively analyzing experiences of the involved faculty. Methods: This study was conducted at Foundation University, Islamabad in six months after ethical approval. In the first phase, resource limitations like time slots, well-equipped rooms, and trained faculty were identified. CBL method was adapted and modified from the Maastricht PBL ‘Seven Jump’ process. 7 CBL sessions were conducted as per the devised method. Semi-structured interviews of 9 CBL facilitators were recorded, transcribed, validated, and analyzed in the second phase. Results: All facilitators believed that these sessions provided a productive, focused, intense yet enjoyable learning experience. 4 considered that large groups hindered adequate student participation, while 2 out of 9 themselves felt nervous due to large class sizes. Recap by the senior faculty member was suggested. Conclusion: Modified CBL sessions were perceived by facilitators as an enjoyable and intense learning opportunity for both students and themselves, despite being conducted in a large group utilizing minimal resources.